2014
DOI: 10.1016/j.ijrobp.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Uveal Melanoma Treated With Iodine-125 Episcleral Plaque: An Analysis of Dose on Disease Control and Visual Outcomes

Abstract: PURPOSE In the treatment of uveal melanomas, the optimal prescribed dose to maximize disease control, but minimize radiation-related complications is unknown. Historically our institution has treated uveal melanomas to doses less than 85 Gy to the tumor apex even if the apex was less than 5mm in height. Here, we investigate how tumor control and visual outcomes are affected by the radiation dose at the tumor apex. METHODS AND MATERIALS A retrospective review was performed to evaluate patients treated for uve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 19 publications
3
52
1
6
Order By: Relevance
“…The latter study suggested that dose to the true apical height may render a lower incidence of radiation-related complications. In another retrospective case study of 190 patients, Perez et al [15] showed data stratified by varied dose quartiles (<65.0 to >85.0 Gy) and reported no association between dose to tumor apex and rate of local failure (9%), which was similar to the COMS trial despite having significantly reduced doses in 50% of their patients. By stratifying their treatment groups to different dose quartiles, they also found a direct relationship between radiation dose and ocular toxicity.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The latter study suggested that dose to the true apical height may render a lower incidence of radiation-related complications. In another retrospective case study of 190 patients, Perez et al [15] showed data stratified by varied dose quartiles (<65.0 to >85.0 Gy) and reported no association between dose to tumor apex and rate of local failure (9%), which was similar to the COMS trial despite having significantly reduced doses in 50% of their patients. By stratifying their treatment groups to different dose quartiles, they also found a direct relationship between radiation dose and ocular toxicity.…”
Section: Discussionmentioning
confidence: 74%
“…Fourteen studies were retrospective clinical chart reviews [14,15,22,23,24,25,26,27,28,29,30,31,32], and 1 was a prospective, randomized trial, the COMS trial [17]. One retrospective study included patients from the COMS trial [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in prescription point from 5-mm point to tumor apex for tumors ! 5 mm thick allows for the reduction of dose to sensitive (18) in which the same approach as prescribing to the apex of tumor was used. Local tumor control at 5 years was 91% comparable to COMS data.…”
Section: Discussionmentioning
confidence: 99%
“…The plaque covered the largest basal dimension of tumor with a radial margin of 2e3 mm. The plaque size was determined for each individual patient as one of following six available plaques: 10,12,14,16,18, and 20 mm. The number of seeds corresponding to each plaque was 5,8,13,13,21, and 24, respectively.…”
Section: Treatment Proceduresmentioning
confidence: 99%